2017
DOI: 10.4172/neuropsychiatry.1000255
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Vitamin D Deficiency: Causality, Assessment, and Clinical Practice Implications

Abstract: Purpose: Carotid dissection is the most important cause of ischemic stroke in young adults. Ischemic stroke rate up to 20% in people under 50 years. Recently, young patients under 50 years of age who were admitted to the emergency department with ischemic stroke complaints were diagnosed with carotid dissection.Methods: For this purpose, cranio-cervical CT angio images of patients admitted to our clinic with suspected carotid artery dissection and diagnosed as ICA dissection were retrospectively reviewed. the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 65 publications
2
23
0
2
Order By: Relevance
“…Many of these regions express 1α-hydroxylase, which converts 25)OH)D to 1,25)OH)2D3, and this explains the autocrine and paracrine properties of this vitamin. 27 Recently, it has been reported that low vitamin D levels are associated with schizophrenia, depression, and anxiety in the general population. 28 In a cohort study conducted between 2015 and 2017, Fond et al 29 reported hypovitaminosis D in 21.4% of the subjects with no vitamin D supplementation during the previous 12 months.…”
Section: Correlations Between the 25(oh)d And Tsh Levels And The Bdi-mentioning
confidence: 99%
“…Many of these regions express 1α-hydroxylase, which converts 25)OH)D to 1,25)OH)2D3, and this explains the autocrine and paracrine properties of this vitamin. 27 Recently, it has been reported that low vitamin D levels are associated with schizophrenia, depression, and anxiety in the general population. 28 In a cohort study conducted between 2015 and 2017, Fond et al 29 reported hypovitaminosis D in 21.4% of the subjects with no vitamin D supplementation during the previous 12 months.…”
Section: Correlations Between the 25(oh)d And Tsh Levels And The Bdi-mentioning
confidence: 99%
“…17 Some study shows correlation between lower vitamin D levels and severe depression, emotional mood symptoms of premenstruation women, adult mood and cognitive disorder. 18,19 Vitamin D administration by supplement and sun ray exposure in one month show the positive effects for affective disorders. 20 Based on this background, a study to find out the influence of vitamin D supplement administration to reduce academic stress is required because the prevalence of the condition in Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…Low levels of vitamin D have been associated with severe depression, moods of premenstrual women, and adult mood and cognitive disorders. 18,19 Two RCTs measuring sun ray exposure vs. vitamin D supplementation for seasonal affective disorder show the positive effects of vitamin D, both by consuming supplements and sun ray exposure during one month. 20 To reduce academic stress, students should consume vitamin D and expose their skin to ultraviolet sun rays for limited amounts of time (note that overexposure to ultraviolet light can cause skin cancer and other bad outcomes).…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, es importante también señalar la importancia que tuvo en este caso el nivel de vitamina D normalizado a la hora de intervenir este tipo de casos, y más en estos pacientes, ya que influye en el proceso de la osteosíntesis en la disminución del riesgo no unión, infección e incluso de la depresión, factor a tener en cuenta tanto por el largo posoperatorio como por la propia patología del paciente 44,45 .…”
Section: Discussionunclassified